Place and Memory in Commemorating Remembrance of George Town UNESCO World Heritage Site - Che Amat, Rohayah; Zainal Abidin, Nor Arbina (TATALOKA, 2024)
This paper seeks to delve into the dynamic interplay between place and memory at the George Town UNESCO World Heritage Site, with a focus on how its physical monuments serve as vessels for collective memory and narrators of the city's history. This study engages with theoretical perspectives of memory and place to analyze commemorative processes and evaluates their role in maintaining cultural continuity and identity.  The study conducted semi-structured interviews and distribute surveys among a carefully selected cross-section of George Town's populace, thus ensuring a representative narrative mosaic. The inquiry will include an assessment of the site and exploring its significance in the community's social fabric. The study recognizes the complexity of interpreting memories within ever-changing urban landscapes and addresses potential biases. Childhood memories, especially when structures remain, shape a person's image of a place. Their tales demonstrate their love for it. The length of a person's relationship with a place most affects their opinion. Long-term residents like it more. Place and memory are vital to commemorating George Town, a UNESCO World Heritage Site. This relationship must frequently be adapted to urban life. The city acknowledges memory interpretation, resolves prejudices about memorial traditions, and embraces inclusive narratives to preserve cultural memory for future generations. The outcomes will offer new insights into conservation strategies and enrich our understanding of historical urban environments.